Formulasi Kebijakan Anggaran Pendidikan dalam Mewujudkan Peningkatan Pemerataan Pendidikan Era Otonomi Daerah di Kabupaten Solok - Putra, Ronni Ekha (Jurnal Demokrasi, 2010)
Post-Reform has brought about a fundamental change in the national education system. Changes in the education system follow changes in the authoritarian system of government-centralized toward decentralized, better known by the name of educational autonomy.Â Thus, the education system also adjusts to model of regional autonomy. PolicyÂ  autonomy in education, then expected to bring much hope for the improvement of education system in the region in particular and in Indonesia as a whole. This study tried to describe the formulation of educational budget policy in Solok Regency and the actors involved in the formulation. The qualitative method was used in this study. Based on data analysis, it is found that autonomy in the regency of Solok has used the bottom-up model in the budget policy formulation, which involves active community participation. The involvement of the community is expected for distribution of education at every level of society. Kata Kunci: Formulasi Kebijakan, Anggaran Pendidikan, Otonomi Daerah, Pemerataan Pendidikan